Upaya Meningkatkan Hasil Belajar Peserta Didik Kelas VI Mapel Pendidikan Pancasila melalui Model Problem Based Learning - Iffana Fatikha Rizqi; Ida Dwijayanti; Qoriati Mushafanah; Erma Khristiyowati (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
It takes a learning model that improves critical thinking skills as a learning resource because this research is focused on students whose learning outcomes are low because the learning model used by the teacher has not been centered on students. The purpose of this study was to improve the learning outcomes of grade VI students of SDN Tambakrejo 01 Semarang in Pancasila education subjects. This study involved 27 students from the class. Classroom Action Research is the type of this study. The research was conducted in three cycles and used the Miles data analysis method, which consists of four stages: planning, action, observation, and reflection. The results showed that the learning outcomes of students averaged 78% in cycle I, 85% in cycle II, and 96% in cycle III, so the researcher determined that this study had achieved success. Therefore, it can be concluded that the use of PBL learning models can improve student learning outcomes. By using a problem-based learning model, differentiated learning makes learning more meaningful because students can easily understand and find the concept of the material that is being studied.